PENGARUH LIKUIDITAS, LEVERAGE, PROFITABILITAS, INVESTMENT OPPORTUNITY SET TERHADAP DIVIDEND PAYOUT RATIO - Herawati, Faradina Eka; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine the influence of liquidity, leverage, profitability and investmentopportunity set to the dividend payout ratio of manufacturing companies which are listed in Indonesia StockExchange (IDX). This research is a quantitative research. The population is all manufacturing companies whichare listed in Indonesia Stock Exchange (IDX) consecutively 5 years from 2011 to 2015. The sample collectiontechnique has been carried out by using purposive sampling and based on the predetermined criteria 37companies have been selected as samples. The data analysis technique has been done by using multipleregressions analysis and the hypothesis test has been carried out by using regression analysis. Based on theresult of model feasibility test shows that the regression models which have been generated are good (feasible) andthese models can be applied for the following analysis. Based on the result of hypothesis test, it shows that thevariables i.e. Current Ratio and Return on Asset gives positive and significant influence to the Dividend PayoutRatio of manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2015 periods.Keywords: Current ratio, debt to equity ratio, return on asset, investment opportunity set, dividend payoutratio.